The EU and its Arctic spirit: Solving Arctic climate change from home?. Issue 2 (October 2019) - Chuffart, Romain; Raspotnik, Andreas
Dealing with climate change and developing the Arctic sustainably are often seen as both binary and contradictory sets of challenges. The EU is in a unique position in Arctic affairs: unlike non-Arctic states, it is part of and linked to the region. However, the EU is at risk of missing the opportunity to be a leader in setting standards for a coherent and sustainable approach for the region. The Arctic is often used as a symbol for global climate change and, conversely, climate change is also used as a reason for more Arctic engagement. Yet, the roots of global heating—greenhouse gas emissions—mostly originate from outside the region. This article asks whether the path towards more EU–Arctic involvement should start closer to home.